Development of Game-based Learning Media Using the Quizwhizzer Application on the Topic of Mathematical Logic - Pratama, Arga Bagus; Rachmawati, Lina; Sulisworo, Dwi (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
This study aims to develop a game-based learning media using the Quizwhizzer application for 12th-grade students at SMK Muhammadiyah 1 Sleman. This product is created based on the analysis of students' needs and issues. Data for the analysis is derived from student surveys and interviews with mathematics teachers. The game-based learning media is developed using the ADDIE model, with the first step being Analysis, the second Design, the third Development, the fourth Implementation, and the fifth Evaluation. The product is developed based on validation results from media and content experts. It is found that the game-based learning media using the Quizwhizzer application falls into the category of highly valid, with an average media expert validation score of 3.00 and content expert validation score of 3.33. Furthermore, student responses indicate that the developed product is highly practical for use among 12th-grade students at SMK Muhammadiyah 1 Sleman, with a practicality percentage of 84.16%. Keywords: Quizwhizzer, Mathematical Logic, Game.